Intrapleural Adenoviral Delivery of Human Plasminogen Activator Inhibitor–1 Exacerbates Tetracycline-Induced Pleural Injury in Rabbits - Karandashova, Sophia (American Thoracic Society, 2013)
Elevated concentrations of plasminogen activator inhibitor–1 (PAI-1) are associated with pleural injury, but its effects on pleural organization remain unclear. A method of adenovirus-mediated delivery of genes of interest (expressed under a cytomegalovirus promoter) to rabbit pleura was developed and used with lacZ and human (h) PAI-1. Histology, β-galactosidase staining, Western blotting, enzymatic and immunohistochemical analyses of pleural fluids (PFs), lavages, and pleural mesothelial cells were used to evaluate the efficiency and effects of transduction. Transduction was selective and limited to the pleural mesothelial monolayer. The intrapleural expression of both genes was transient, with their peak expression at 4 to 5 days. On Day 5, hPAI-1 (40–80 and 200–400 nM of active and total hPAI-1 in lavages, respectively) caused no overt pleural injury, effusions, or fibrosis. The adenovirus-mediated delivery of hPAI-1 with subsequent tetracycline-induced pleural injury resulted in a significant exacerbation of the pleural fibrosis observed on Day 5 (P = 0.029 and P = 0.021 versus vehicle and adenoviral control samples, respectively). Intrapleural fibrinolytic therapy (IPFT) with plasminogen activators was effective in both animals overexpressing hPAI-1 and control animals with tetracycline injury alone. An increase in intrapleural active PAI-1 (from 10–15 nM in control animals to 20–40 nM in hPAI-1–overexpressing animals) resulted in the increased formation of PAI-1/plasminogen activator complexes in vivo. The decrease in intrapleural plasminogen-activating activity observed at 10 to 40 minutes after IPFT correlates linearly with the initial concentration of active PAI-1. Therefore, active PAI-1 in PFs affects the outcome of IPFT, and may be both a biomarker of pleural injury and a molecular target for its treatment.